Loneliness and psychosocial outcomes among left-behind learners in child-only households in South Africa - Jaure, Ricanos; Makura, Alfred Henry (Interdisciplinary Journal of Sociality Studies, 2025)
Parental labour migration in South Africa has led to an increasing number of left-behind learners residing in child-only households. This separation disrupts familial structures and adversely affects children’s psychosocial well-being and academic performance. This study aims to investigate how loneliness manifests among left-behind secondary school learners and influences their emotional, behavioural, and educational outcomes within both school and community contexts. A qualitative case study design was employed at one secondary school in South Africa. Fourteen left-behind learners and twelve community and educational informants were purposively selected to participate in focus group discussions and follow-up interviews. Data were analysed thematically. Findings indicate that loneliness has significant emotional repercussions, including heightened sadness, anxiety, and low self-esteem. Behaviourally, learners exhibit withdrawal, aggression, and risk-taking due to limited or absent parental supervision. Academic performance is negatively impacted by diminished motivation, concentration difficulties, and absenteeism. Furthermore, negative stereotypes within the community and school exacerbate learners’ isolation and restrict access to supportive networks. In conclusion, loneliness emerges as a critical psychosocial risk factor that undermines the holistic well-being and educational experiences of left-behind learners. The study recommends the implementation of school and community-based support initiatives to enhance emotional care, social inclusion, and academic participation.